Comparative in vitro activity of ceftaroline and comparator agents against nosocomial Gram-negative and Gram-positive clinically significant bacterial isolates from patients in a teaching hospital in Kuwait. (19th May 2018) - Jamal, Wafaa; Abdulkareem, Hayfaa; Rotimi, Vincent O.
Abstract : The objective was to test the in vitro activities of ceftaroline and comparator agents against clinical isolates of Gram-negative and Gram-positive bacteria. Isolates were identified with VITEK II. Susceptibility testing was with E test. A total of 1264 isolates were tested. Compared to other cephalosporins, ceftaroline demonstrated excellent in vitro activities (MIC90, ≤0.5 mg/L) against Escherichia coli, Salmonella spp. and Haemophilus influenzae . When matched with the comparator cephalosporins, ceftaroline demonstrated the greatest activity against methicillin-susceptible Staphylococcus aureus (MSSA), with MIC90 of 0.25 mg/L. Ceftaroline's MIC90 s against both community-associated methicillin-resistant S. aureus (MRSA) and hospital-acquired MRSA were 0.5 and 1 mg/L, respectively. Major discrepancies were noted between E test and disc diffusion tests for ceftaroline only against 16 Gram-negative and 16 Gram-positive isolates. Ceftaroline demonstrated an excellent in vitro activity against the majority of clinically significant Gram-negative and Gram-positive isolates obtained from proven cases of bacterial infections.